Discusiones acerca del concepto de sociología jurídica (2018)
Every day the juridical sociology or sociology of the law gets more importance in the field of law sciences. This importance takes root in the perspectives of analysis that juridical sociology offers to the study of the laws and its relationships with the social phenomena. Nevertheless, as a subjetc of early formation, there is a contrversy about the concept an the object of juridical sociology. From a comparative point of view this article presents the contributions of academicians of Europe and America to those object and concept.